PENGARUH MOTIVASI PESAN DAN PENYAJIAN BUKLET TERHADAP PERSEPSI DAN PENGETAHUAN TENTANG JAJANAN SEHAT - Djamaludin, Moh. Djemdjem; Simanjuntak, Megawati; Rochimah, Nur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
The aims of this research was to analyze the influence of message appeals and booklet presentation toward children’s perception and knowledge about healthy streetfood. This research involved 77 students of fifth grade in elementary school that were selected randomly. The design of this research was 2 (message appeals: positive vs negative appeals) x 2 (booklet presentation: with and without explanation) factorial design with pretest and posttest. Result revealed that message appeals and booklet presentation did not influence children’s perception and knowledge about healthy streetfood. However, result also indicated that the combination of positive appeals and booklet presentation without explanation could increase children’s perception about healthy streetfood. Otherwise, knowledge about healthy streetfood increased when children treated by booklet with negative appeals and given the explanation.